2016
DOI: 10.1063/1.4941540
|View full text |Cite
|
Sign up to set email alerts
|

The origins of near band-edge transitions in hexagonal boron nitride epilayers

Abstract: Photoluminescence spectroscopy has been employed to probe the near band-edge transitions in hexagonal BN (h-BN) epilayers synthesized under varying ammonia flow rates. The results suggest that the quasi-donor-acceptor pair emission line at 5.3 eV is due to the transition between the nitrogen vacancy and a deep acceptor, whereas the 5.5 eV emission line is due to the recombination of an exciton bound to a deep acceptor formed by carbon impurity occupying the nitrogen site. By growing h-BN under high ammonia flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31] Based on the photoluminescence (PL) emission spectroscopy studies performed on unintentionally doped h-BN epilayers grown under varying NH 3 flow rates (hence with controlled V N concentrations) 32,33 and theoretical insights, [24][25][26][27][28] it is now understood that V N are shallow donors with an activation energy of about 0.1 eV, whereas C N are deep acceptors having two activation energies of about 2.3 and 1.1 eV. 32,33 On the other hand, experimental studies on the properties of intentional doped impurities have been limited for h-BN. 4,5,[34][35][36] Prior studies seem to indicate that p-type conductivity is easier to realize in h-BN than in AlN via Mg doping, revealing the potential of h-BN to extending p-type III-nitride materials all the way up to 6 eV.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] Based on the photoluminescence (PL) emission spectroscopy studies performed on unintentionally doped h-BN epilayers grown under varying NH 3 flow rates (hence with controlled V N concentrations) 32,33 and theoretical insights, [24][25][26][27][28] it is now understood that V N are shallow donors with an activation energy of about 0.1 eV, whereas C N are deep acceptors having two activation energies of about 2.3 and 1.1 eV. 32,33 On the other hand, experimental studies on the properties of intentional doped impurities have been limited for h-BN. 4,5,[34][35][36] Prior studies seem to indicate that p-type conductivity is easier to realize in h-BN than in AlN via Mg doping, revealing the potential of h-BN to extending p-type III-nitride materials all the way up to 6 eV.…”
mentioning
confidence: 99%
“…7,20 Most recent studies have suggested that the D-series emission lines are due to the recombination of excitons bound to deep acceptors formed by carbon impurities occupying the nitrogen sites, and h-BN epilayers exhibiting pure intrinsic FX emission can be obtained by growing the materials under high ammonia flow rates. 21 However, the detailed features of the FX transitions in h-BN epilayers are distinctly different from those in h-BN bulk crystals, 21 which is what remains to be investigated and understood. Currently, bulk h-BN crystals are small (less than 1 mm by 1 mm), [3][4][5]13,15 but the basic properties measured from the bulk materials set the benchmarks for the further development of wafer scale epilayers.…”
mentioning
confidence: 99%
“…Du et al, studied effects of V/III ratio on the luminescence properties of MOCVD-grown h-BN and succeeded in synthesizing h-BN epitaxial layers without emission at around 300 nm which is known to be from impurities such as C and O. 14 Meanwhile, carrier gas is also an important factor determining properties of semiconductors grown by chemical vapor deposition (CVD) method including MOCVD growth, especially for atomically thin and flat 2D materials since it strongly affects the gas phase chemical reaction influencing growth rate, surface morphology and crystallinity of the grown film. There are several reports on the evolution of h-BN crystal under different gas ambient with and without nitrogen (N), in which the carrier gas is considered as a source of N atoms.…”
mentioning
confidence: 99%
“…11 In addition, h-BN was also proposed as an active material for an ultraviolet light emitter replacing the conventional Hg-vapor-based lamps or AlGaN-based ultraviolet light-emitting diodes (LEDs) due to its strong light-matter interaction originating from the 2D nature. 4,5,[12][13][14] In the industrial perspective, wafer-scale growth of 2D materials becomes one of the most critical issues. Metal-organic chemical vapor deposition (MOCVD) has been proposed as a very promising solution to achieve wafer-scale growth of h-BN on sapphire or other substrates, since Y.…”
mentioning
confidence: 99%